2020
DOI: 10.1007/s11548-020-02249-1
|View full text |Cite
|
Sign up to set email alerts
|

A learning-based method for online adjustment of C-arm Cone-beam CT source trajectories for artifact avoidance

Abstract: Purpose During spinal fusion surgery, screws are placed close to critical nerves suggesting the need for highly accurate screw placement. Verifying screw placement on high-quality tomographic imaging is essential. C-arm cone-beam CT (CBCT) provides intraoperative 3D tomographic imaging which would allow for immediate verification and, if needed, revision. However, the reconstruction quality attainable with commercial CBCT devices is insufficient, predominantly due to severe metal artifacts in the presence of p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 30 publications
0
33
0
Order By: Relevance
“…Wu et al [15] compared MAR with different C-arm trajectories in reducing blooming artifacts on CBCT reconstructions and demonstrated that non-circular orbits reduced metal artifacts by 46% compared to circular orbits. Thies et al [16] introduced a MAR technique that uses non-circular C-arm orbits with intraoperative adjustments of X-ray source trajectory to optimize the image reconstruction quality. These adjustments are based on a machine-learning algorithm using convolutional neural networks, which can predict quality metrics that enable scene-specific adjustments of the CBCT source trajectory, thus improving the image quality and reducing metal artifacts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al [15] compared MAR with different C-arm trajectories in reducing blooming artifacts on CBCT reconstructions and demonstrated that non-circular orbits reduced metal artifacts by 46% compared to circular orbits. Thies et al [16] introduced a MAR technique that uses non-circular C-arm orbits with intraoperative adjustments of X-ray source trajectory to optimize the image reconstruction quality. These adjustments are based on a machine-learning algorithm using convolutional neural networks, which can predict quality metrics that enable scene-specific adjustments of the CBCT source trajectory, thus improving the image quality and reducing metal artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…This method can also be extended by known-component image reconstruction [13,14]. Another technique uses optimized C-arm orbits in order to avoid collinearity between the X-ray source and screws [15,16]. Figures 1 and 2 demonstrate ARSN images for the baseline technology without MAR (NoMAR) in comparison to images using MAR, which is based on the interpolation of projection data neighboring the metal shadow around the pedicle screw [10].…”
Section: Introductionmentioning
confidence: 99%
“…In many other -from a research perspective perhaps more exciting -cases, this retrospective data collection paradigm is infeasible because the task to be performed with a machine learning algorithm is not currently performed in clinical practice. The more obvious examples are visual servoing of novel robotic surgery platforms [88] or robotic imaging paradigms that alter how data is acquired [93,94]. Despite the fact that most studies included in this review address use-cases that fall under the "opportunity cost" category, we found that only 16 out of the 48 studies used real clinical or cadaveric data to train the machine learning algorithms.…”
Section: Preserving Improvements Under Domain Shift From Training To ...mentioning
confidence: 99%
“…In many other—from a research perspective perhaps more exciting—cases, this retrospective data collection paradigm is infeasible because the task to be performed with a machine learning algorithm is not currently performed in clinical practice. The more obvious examples are visual servoing of novel robotic surgery platforms ( Gao et al, 2019 ) or robotic imaging paradigms that alter how data is acquired ( Zaech et al, 2019 ; Thies et al, 2020 ). Despite the fact that most studies included in this review address use-cases that fall under the “opportunity cost” category, we found that only 16 out of the 48 studies used real clinical or cadaveric data to train the machine learning algorithms.…”
Section: Perspectivementioning
confidence: 99%